Optimizing User Satisfaction: Exploring The Impact Of Website Quality On Low Vision Disabled Students' Satisfaction Through User Experience As A Mediating Variable - Rahmah, Yusriyah; Aknuranda, Ismiarta; Ratnawati, Dian Eka (MSJ : Majority Science Journal, 2024)
This research investigates the correlation between service quality, user experience, and user satisfaction in website design for students with low vision disabilities undergoing final assignment guidance at Brawijaya University. Using a quantitative approach via questionnaires, data was collected from students and relevant academics at the Disability Service Center. Analysis revealed a positive and significant relationship between service quality and user experience, with service quality also impacting user satisfaction. Moreover, user experience partially mediated the relationship between service quality and user satisfaction. This study contributes to understanding the dynamics of website design for this demographic, emphasizing the pivotal role of user experience in enhancing satisfaction, particularly among individuals with disabilities. Organizations, especially Disability Service Centers, can utilize these findings to enhance website accessibility and academic support. However, limitations include sample size constraints and the singular institutional focus, suggesting avenues for future research to broaden the scope and depth of understanding through qualitative methods.